On Depth and Retrospect: “I Forget, and Forgive – but I Discount” - Ana Paula Martins (Economics and Econometrics Research Institute (EERI), 2007)
The discounting of future felicity flows transposes to the intertemporal optimization context the assumption of interest-bearing wealth or savings. The validity of the hypothesis has been challenged by several empirical (ir)regularities and by the theoretical implications for human decision processing. In particular, it implies a very special weight of past decisions on current welfare prospects, which appears largely inconsistent with forgetfulness – even if not with learning – and memory effects, often stressed or embedded in behavioral science studies. In this article, we explore the modifications induced by generalizing the typical welfare function in order to accommodate such retrospective influences. The idea is simple – and can be thought inspired in felicity functions encompassing habit formation: to allow for accumulated welfare – of hypothetically “compounded” but also depreciating past-to-current felicity streams – to affect the periodic utility function – which therefore enjoy some durable good properties. Sensitivity of the Ramsey optimal path to the new formulation is also inspected. The mathematical principle has useful production theory applications: in supply chain modelling. Then the optimal depth of a production process stems from a standard problem that now also embeds delay evaluation – discounting; a rationale for a particular pattern of the term structure of interest rates was also forwarded. Growth – general equilibrium - models are extended to allow for the hypothesis.
Keywords: D90; E40; E43; G00; C61; O40; L22; D85; 330; Time Discount; Time Preference; Interest; Retrospect Theory; Durable Goods; Durable Felicity Functions; Vertical Production Systems; Intertemporal Economies of Depth; Supply Chains; Networks; Complexity; Consistency; Term Structure of Interest Rates